The Relationship Between Motivation and Learning Outcomes of Biology Subject Through Distance Learning - Salsa, Feni Julia; Sari, Rona Taula; Muhar, Nawir; Gusmaweti, Gusmaweti (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
This study aimed to determine the relationship between motivation and biology learning outcomes through distance learning in senior high school in Indonesia. The change in the face-to-face learning process to distance learning since the Covid-19 pandemic has had an impact on learning motivation that affects student learning outcomes. This type of research is descriptive with quantitative research methods. The research was conducted at one high school in Indonesia. The research subject consist of 80 students. The sampling technique was simple random sampling, which was done randomly, using an error rate of 5%. The data collection in this study used a questionnaire containing statements of students' learning motivation through distance learning using a Likert scale, and documents on students' biology learning outcomes in the odd midterm exams for the 2021/2022 academic year. The results of the Pearson product moment correlation test were obtained at 0.86 on intrinsic motivation and extrinsic motivation of 0.85, meaning that there is a relationship between motivation and biology learning outcomes through distance learning. The results of the t-test showed that the t-count of intrinsic motivation was 15.27 and the t-count of extrinsic motivation was 14.47, indicating that there was a significant relationship between motivation and learning outcomes of biology subject through distance learning. The coefficient of determination of intrinsic motivation is 75% and extrinsic motivation is 73%, this means that intrinsic motivation (X1) and extrinsic motivation (X2) contribute to student biology learning outcomes (Y).